Anthropometric indicators of body image dissatisfaction and perception inconsistency in young rhythmic gymnastics - Zaccagni, L.; Rinaldo, N.; Gualdi-Russo, E. (Asian Journal of Sports Medicine, 2019)
Background: Although the positive effects of sports on body image perception are well described in the literature, rhythmic gymnasts have been reported to be at greater risk of developing body dissatisfaction and possibly eating disorders. The reason is that athletes engaged in aesthetic sports may be subject to greater pressure to be thin in order to adhere to the norms of that sport.